2013
DOI: 10.1021/la401035p
|View full text |Cite
|
Sign up to set email alerts
|

Isosteric Heats of Gas and Liquid Adsorption

Abstract: The heat of adsorption is an indicator of the strength of the interaction between an adsorbate and a solid adsorbent. This parameter can be determined from the heat released in calorimetric experiments or from the analysis of adsorption isotherms at different temperatures. The latter, called isosteric heats of adsorption, are commonly used in the characterization of materials for gas- and liquid-phase adsorption. Although the equations for the determination of isosteric heats of adsorption from the gas phase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 11 publications
0
64
3
Order By: Relevance
“…This parameter can be calculated from heat released in calorimetric experiment and from the analysis of adsorption isotherm at different temperatures. Heat of adsorption determined by the latter technique is called isosteric heats of adsorption, which is generally used in the characterization of adsorbents material for gas and liquid phase adsorption (Builes et al 2013). Information about Q st is very important, particularly during gaseous phase adsorption because the heat released upon adsorption is partially adsorbed on the adsorbent, which causes a rise in the adsorbent temperature and influences the adsorption equilibrium and kinetics and thus, as a result, the overall gas adsorption capacity of the adsorbent (Martin et al 2011).…”
Section: Heat Of Co 2 Adsorption Of the Adsorbentsmentioning
confidence: 99%
“…This parameter can be calculated from heat released in calorimetric experiment and from the analysis of adsorption isotherm at different temperatures. Heat of adsorption determined by the latter technique is called isosteric heats of adsorption, which is generally used in the characterization of adsorbents material for gas and liquid phase adsorption (Builes et al 2013). Information about Q st is very important, particularly during gaseous phase adsorption because the heat released upon adsorption is partially adsorbed on the adsorbent, which causes a rise in the adsorbent temperature and influences the adsorption equilibrium and kinetics and thus, as a result, the overall gas adsorption capacity of the adsorbent (Martin et al 2011).…”
Section: Heat Of Co 2 Adsorption Of the Adsorbentsmentioning
confidence: 99%
“…The adsorption constant is a function of temperature, the enthalpy and entropy of adsorption, furthermore, the dependence that K ad has on temperature can be determined if the enthalpy of adsorption is known. The determination of the enthalpy or heats of adsorption from the liquid phase has been acknowledged to be more challenging than for adsorption from the gaseous phase 50 In the literature, the studies of isosteric heats of adsorption in the liquid phase have often reported low values. 50 -52 Hence, in the present work it is assumed that the heat of adsorption is relatively low, implying that for the studied temperature range the effect that temperature has on the K ad value is low enough such that it can be considered negligible.…”
Section: Kinetic Modelingmentioning
confidence: 99%
“…In addition, using the adsorption isotherms at various temperatures, the isosteric heat of adsorption can be determined. e isosteric heat of adsorption, also called enthalpy of adsorption (ΔH ads ), indicates the strength of the interaction (bond) between the adsorbate (water molecules) and the solid adsorbent [71,72]. is parameter represents the energy necessary for the heat of vaporization of moisture in a material during the adsorption process to exceed the latent heat of vaporization of pure water at a certain temperature [73].…”
Section: Water Sorption Analysismentioning
confidence: 99%